26. EVALUATION OF THE EFFECT OF CATGUT IMPLANT METHOD COMBINED WITH “HOAN LUC VI” IN TREATMENT OF TRADITIONAL MEDICINE SYMPTOMS OF LUMBAR PAIN CAUSED BY DEFICIENCY YIN KIDNEY (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluate the effectiveness of the catgut implant method combined with “Hoan Luc vi” in the treatment of traditional medicine symptoms of lumbar pain caused by deficiency yin kidney. Subjects andMethods: Study design: a prospective study, interventional design, beforeafter treatment comparison, and controlled. 50 patients regardless of sex and occupation were diagnosed with lumbar pain due to a deficiency yin kidney at Ho Chi Minh Institute of National Medicine and Pharmacy from May 2020 to October 2021.Results: No back pain accounted for 40%; 48% no knee fatigue or only mild knee fatigue; 32% mild tinnitus or no tinnitus, no more nocturia accounted for 48%; patients no longer have vexing heat in the chest, palms, and soles accounted for 48%; 8% no tidal fever; 22% no steaming bone and 60% no longer night sweating.Conclusion: catgut implant method combined with “Hoan Luc vi” is effective in treating traditional medical symptoms of patients with deficiency yin kidney.
Keywords: Lumbar pain; catgut implant; deficiency yin kidney; Hoan Luc vi